Efficacy of Peep-Zeep Manoeuvre, Ventilator Hyperinflation and Conventional Chest Physiotherapy on Ventilator-Associated Pneumonia: A Pilot Study - Dr. Vaishnavi Yadav , Dr. Vishnu Vardhan , Dr. Sourya Acharya , Dr. Hemant Deshpande (South Eastern European Journal of Public Health, 2025)
Ventilator-associated pneumonia is one of the major complications in patients submitted to a mechanical ventilator. Prevention and removal of pulmonary secretion, which is one of the primary causes of pneumonia, is a challenge for physiotherapists due to the presence of constant positive pressure. Conventional chest physiotherapy techniques, including suctioning, have certain disadvantages, such as no optimum intrapulmonary effect and effective flow bias generation, which is essential to propel secretions towards the central airway. Thus, the present study aims to evaluate the efficacy of PEEP-ZEEP manoeuvre, ventilator hyperinflation and conventional chest physiotherapy on ventilator-associated pneumonia. The objectives of the study are to evaluate and compare the effect of all the interventions on Clinical Pulmonary infection score (CPIS), oxygenation level (PaO2/FIO2), dynamic compliance, extubation day and length of ICU stay. Method: 36 mechanically ventilated patients were randomly allocated to three groups for intervention. Group A chest physiotherapy with PEEP-ZEEP Manoeuvre, Grou B chest physiotherapy with ventilator hyperinflation and conventional chest physiotherapy. Result: There was a significant difference in clinical pulmonary infection score (Group A p 0.002, Group B 0.000, Group C 0.00), Pao2/fio2 (Group A p =0.00, Group B p=0.000, Group C p 0.000), Fio2 (Group A p 0.002, Group B p= 0.00, Group C p= 0.0033), dynamic compliance (Group A p= 0.000, Group B p= 0.00, Group C p= 0.000), sputum (Group A p= 0.000, Group B p= 0.00, Group C p= 0.000) within the groups using t-test. There was no significant difference in clinical pulmonary infection score when pre-post difference scores were compared between the groups (Group A vs Group C p= 0.52, Group B vs Group C p=0.07, Group A vs Group B p= 0.096). There were no significant differences for Pao2/fio2 (p= 0.1), Fio2 (p= 0.5), dynamic compliance (p=0.9), sputum (p= 0.7) but significant difference for CPIS (p=0.04) between group using ANOVA. Conclusion: Conventional chest physiotherapy and chest physiotherapy along with the ventilator manoeuvre is effective in improving oxygenation, respiratory mechanics and CPIS, i.e. ventilator-associated pneumonia recovery, but the superiority of any intervention needs further study.